Praetorius Versus Zarlino: The Question of Modes - Nejc Sukljan (De Musica Disserenda, 2019)
This article deals with the question of modes as it is discussed in Gioseffo Zarlino’s Istitutioni harmoniche and Michael Praetorius’s Syntagma musicum. First, Gioseffo Zarlino’s adoption of Heinrich Glarean’s system of twelve modes is presented, along with the changes he introduced. Gioseffo Zarlino’s system is then compared to that of Michael Praetorius.